Changes of the calcium ions (Ca++) level and platelet count among donor in plateletpheresis - Salomo Fajar Siahaan; Zulfikar Lubis; Ratna A Ganie (Fakultas Kedokteran USU, 2012)
Background : Application technology for apheresis blood donation appears as part of progress towards therapeutic blood components. Apheresis developed from the desire to get a certain fraction of blood to meet the needs of the patient. Therapeutic apheresis comes from the perception that the ability to separate blood into its components quickly and directly can be given to patients to help the healing process of disease.Methods : Blood taken from a vein into a tube just as regular blood donors which the tube directly connected to a machine. This machine has the ability to turn the blood very quickly. Because the blood cells have different types of specific gravity so it will be divided into several components by specific gravity of erythrocytes, leukocytes, platelets and blood plasma is composed of protein and electrolytes. Retrieval of component blood donor in accordance with the needs and the rest is returned to the donor.Results : The number of subjects is 36 donors. The mean value for variable calcium ions levels that prior to apheresis obtained 1155 (SD 0.088) and after apheresis procedure the mean value obtained 1030 (SD 0.122). From these data found significant difference decrease in levels of calcium ions before and after plateletpheresis (P <0.0001). For a variable platelets count prior to apheresis procedure the mean value obtained 302.74 (SD 44.228) and after apheresis procedures the mean value obtained 209.33 (SD 46,717). From these data found differences significant decrease in the number of platelets before and after plateletpheresis (P <0.0001). For variable haemoglobin the mean value prior the procedure apheresis obtained 15.80 (SD 1214) and after procedure apheresis the mean value obtained 14,957 (SD 1538). Have significant differences between decrease of haemoglobin before and after plateletpheresis (P <0.0001).Conclusion : This research obtained meaningful decline in the levels of Ca++, platelets count and haemoglobin levels after plateletpheresis, the cycles of plateletpheresis is tied to platelets count prior to plateletpheresis. Eleveted platelets count before plateletpheresis, then the less of cycles performed on apheresis.Keywords : Apheresis; calcium Ions; platelets; haemoglobin.